Review of the Japanese Microtendipes (Diptera: Chironomidae: Chironominae), with description of a new species - Tang, Hongqu; Niitsuma, Hiromi (Zootaxa, 2017)
Japanese species of Microtendipes are reviewed. Eleven names proposed in this genus, including Russian M. sakhalinensis Zorina, 2001, are synonymized with M. umbrosus Freeman, 1955, for which male and female adults, pupa and larva are redescribed based on specimens collected from Japan. Two species, M. shoukomaki Sasa, 1989 and M. famiefeus Sasa, 1996, are validated based on the re-examination of type specimens and are redescribed based on specimens newly collected from Japan. Descriptions of the larva of M. shoukomaki and the female adult, pupa and larva of M. famiefeus are given here for the first time. Microtendipes chloris (Meigen, 1818) sensu Sasa is redescribed as a new species, M. parachloris Niitsuma & Tang sp. nov., based on the male adult. Additionally, synonymic notes of Polypedilum (Cerobregma) yamasinense (Tokunaga, 1940) comb. nov. and P. (Polypedilum) tsukubaense (Sasa, 1979), transferred from Microtendipes, are given. Polypedilum kamotertium Sasa, 1989 and M. iriocedeus Sasa & Suzuki, 2000 are synonymized with the above two species, respectively, based on each original description.         The distribution of M. umbrosus extends from Africa to the Russian Far East and East Asia (Japan, China), and Australia and Thailand (with new distributions reported here). Although no African type material is examined here, the morphological features of those populations are consistent with Freeman’s concept.